Menstrual pattern amongst adolescent girls: a cross sectional study from Raichur, Karnataka - Marri, Pavani; Ravipati, Monisha Deepika; Bolla, Lavanya; Takalkar, Anant A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Menstrual disorders in adolescent age are quite different than in adult women, both for diagnostic and therapeutic management. We need to take into account the problems in normal initiation of menarche, hematological problems, general endocrine problems, and fragile emotional status at this tender age. The objective of the study was to study the patterns of menstrual disorders in adolescent girls. Methods: Cross sectional observational study was carried out in 200 adolescent girls, aged 12 to 19 years, among the students of S.R.P.S PU college and the district government Girls’ school in Raichur during the period of January 2017 to December 2017. A pre-structured questionnaire was used and data was analysed using Statistical package for social sciences (SPSS) 23.0 version. Results: Majority of the girls in our study were from 17-18 years age group (55%). The mean age of menarche was 13.2±0.9 years. Cycle length of <21 days was found in 4 (2%) of cases, 143 (71.5%) had 21-35 days cycle and 10 (5%) had >35 days cycle length. Majority had normal cycle length. Dysmenorrhea was found in 84 (42%) students. Premenstrual symptoms like tiredness were noted in 14 (7%) of cases, pain in the legs in 10 (5%), irritability in 8 (4%), lack of interest in work and play in 7 (3.5%), low back pain in 6 (3%), low/depressed mood in 6 (3%), anger in 4 (2%), anxiety in 4 (2%), difficulty in concentrating in 2 (1%), nauseawere noted in 2 (1%). Conclusions: Prevalence of dysmenorrhea was 42%. Premenstrual symptoms like tiredness were noted in majority of the girls 7%, pain in the legs in 5%, irritability in 4%.